Refining a Video and Text Message Intervention (STAR, Skills Training in Active Recovery) to Prevent the Onset or Escalation of Posttraumatic Stress and Opioid Misuse Among Recent Sexual Assault Survivors: Community Engaged Study - Kate Walsh; Anne Marie Schipani-McLaughlin; Cynthia Stappenbeck; Shahzarin Khan; Anna Woodworth; Sanika Panwalkar; Ronald Acierno; Amanda K Gilmore (JMIR Formative Research)
Abstract BackgroundSexual violence is prevalent, and the consequences can be chronic and impairing. However, few interventions exist to prevent the onset or escalation of posttraumatic stress symptoms and opioid misuse among recent sexual violence survivors. ObjectiveThis study describes a collaborative process of updating an integrated postsexual assault video and developing an SMS text messaging intervention program with a community advisory board (CAB) of sexual assault survivors. MethodsResearch team members met virtually for six 60‐90-minute meetings with a 5-member CAB of sexual assault survivors with diverse racial and gender identities located throughout the United States. CAB members provided feedback on written documents detailing an adapted video script and newly developed text intervention to address the risk of substance misuse and posttraumatic stress disorder symptoms following sexual assault. CAB members also received SMS text messages to provide feedback from the end-user perspective. ResultsWe identified overarching themes to improve relatability (destigmatize and increase awareness of support, reduce technical language, and increase representation in actors), content (increase social support, include substance-related assault, and suggest activities), and wording (normalize different terms for sexual assault and reduce insensitive language) for the video intervention. For the text intervention, we identified themes relating to acceptability (timing, frequency, and format of texts), relatability (having an avatar introduce the program and identifying the study name in messages), content (messaging), and wording (increasing clarity). ConclusionsFindings reinforce the importance of including community members’ perspectives and suggestions to improve the acceptability and relatability of interventions, including the video and SMS text message intervention described here.